Questions of informal caregivers of children regarding the postoperative period of cochlear implant - Raissa Janine de Almeida; Gabriela Fávaro Marques da Cunha; Eliane Alves Motta Cabello dos Santos; Gesiane Cristina Bom; Juliana Silvério Campanati Mendonça; Armando dos Santos Trettene
ABSTRACT Objective: To identify the main questions of informal caregivers of children with hearing impairments on the postoperative care of cochlear implant. Method: Cross-sectional study developed in a public and tertiary hospital of the state of São Paulo, Brazil. The sample consisted of 48 informal caregivers who were monitoring children subjected to cochlear implant. Data collection took place during the preoperative nursing consultation, by structured interview, between September 2016 and July 2017. The questions identified were categorized by similarity. Results: The questions were related to: rest, dressing, feeding, length of stay, system activation time, infection, removal of stitches, bleeding, medicines, immediate sound stimulation, and pain. Conclusion: The prevalent questions were about rest, dressing, and feeding, and identifying them made it possible to plan and implement a nursing care aimed at the caregiver needs, as well as prepare them for care maintenance after hospital discharge.